Acute and sustained molecular changes in synovial fluid following acute knee injury mirror the murine joint injury response - Watt, F; Paterson, E; Freidin, A; Saklatvala, J; Williams, A; Vincent, A (Elsevier, 2014)
Acute joint injury predisposes to OA, and is an ideal setting in which to study early disease pathogenesis. We have shown that an immediate inflammatory response occurs in connective tissues after injury, and a discrete group of mRNAs is up-regulated within hours of medial meniscal destabilisation (DMM) of the mouse joint. Some of this molecular response appears necessary for subsequent OA. We investigated a) whether these same molecules were up-regulated in the joint, and in the blood in the analogous human setting of acute knee injury, and b) how this molecular response varies, between individuals and over time.